Etude phytochimique et l’évaluation de l’effet antilithiasique des extraits de Zizyphus lotus L Et Retama monosperma L - KHALFALLAH, Kawther; BEKADDOUR Mohamed Mounir (My University, 2025)
This work is part of the research on natural alternatives for the treatment of urinary lithiasis. It aims at the phytochemical study of two plant species traditionally used against urinary lithiasis, namely, Zizyphus lotus L and Retama monosperma L, as well as the evaluation of the antilithiasis effect of their extracts prepared by decoction, infusion and maceration. Qualitative phytochemical tests made it possible to detect the presence of several metabolites from which saponosides, reducing sugars tannins and free quinones are strongly present in the three Zizyphus lotus L extracts, while the Retama monosperma L species is rich in flavonoids, polyphenols, tannins, saponosides and reducing compounds especially in the infusion extract. The study of the evolution of pH and the variation in the weight of phosphatic and cystinic urinary stones incubated in vitro with the different extracts, shows a variability between the two species from which the most effective extracts, in particular the decoction of the crust of Zizyphus lotus L and the decoction of Retama monosperma L, showed a notable capacity to reduce the weight of stones and to modify the urinary pH, this activity is attributed to the richness in bioactive metabolites with litholytic properties, these results could be a database for further research in the pharmacological field encouraging their valorization as a potential source of natural treatments against urinary lithiasis.
Keywords: Urinary lithiasis, phytochemical study, Zizyphus lotus L, Retama monosperma L, litholytic activity